2022
DOI: 10.2147/oaem.s368324
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Orthopedic Injuries Related to Road Traffic Accidents Among Patients Managed at the Emergency Department in Black Lion Hospital, Addis Ababa, Ethiopia, 2021

Abstract: Background Studies showed that each year people lose their life on the road and many people are disabled. The majority of this disability was caused by orthopedic injury related to road traffic accidents. However, in the context of Ethiopia, studies ascribed to orthopedic injuries related to road traffic accidents are limited. The study aimed to assess the pattern of orthopedic injuries related to road traffic accidents among patients managed at the emergency department of Black Lion Hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…A comprehensive assessment was conducted to determine the demand for microsurgery services in the local healthcare setting. As previously mentioned, the demand for free flap procedures is notably high in our developing country due to factors such as an increased incidence of motor vehicle accidents (6), a high prevalence of NOMA (7), and delayed presentations of head and neck cancers (5). Interviews with surgeons from various units in the medical center revealed that, on average, approximately 50 cases per year required flap coverage, with a quarter of these cases necessitating free flap procedures, often resulting in limb amputation in the orthopedic department.…”
Section: Identifying the Demand For Microsurgery Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive assessment was conducted to determine the demand for microsurgery services in the local healthcare setting. As previously mentioned, the demand for free flap procedures is notably high in our developing country due to factors such as an increased incidence of motor vehicle accidents (6), a high prevalence of NOMA (7), and delayed presentations of head and neck cancers (5). Interviews with surgeons from various units in the medical center revealed that, on average, approximately 50 cases per year required flap coverage, with a quarter of these cases necessitating free flap procedures, often resulting in limb amputation in the orthopedic department.…”
Section: Identifying the Demand For Microsurgery Servicesmentioning
confidence: 99%
“…tissue defects. This is particularly relevant in sub-Saharan Africa, characterized by a heightened incidence of motor vehicle accidents, 5 high incidence of NOMA (necrotizing disease that destroys the mouth and the face), 6 and delayed presentations of head and neck cancers. 7 In a sub-Saharan African nation like Ethiopia, where approximately 120 million people lack access to microsurgery, there is a consequential impact on patients, resulting in considerable disability and heightened morbidity.…”
mentioning
confidence: 99%
“…Research reveals that the perception hazards, vulnerable groups, young, careless, and inexperienced drivers cause more accidents, [25,26]. They have prototype patterns of injuries, [27]. The legal low drinking age and blood alcohol concentration (BAC) of drivers are susceptible to deaths and particularly at night.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Burns can also occur during an explosion following an accident or minor burns due to contact with high-temperature vehicle parts, such as exhaust (Ramadhani, 2019;Bezabih, 2021).…”
Section: Abrasionsmentioning
confidence: 99%